Impact of Weekly Community-Based Dance Training Over 8 Months on Depression and Blood Oxygen Level–Dependent Signals in the Subcallosal Cingulate Gyrus for People With Parkinson Disease: Observational Study - Karolina A Bearss; Rebecca E Barnstaple; Rachel J Bar; Joseph F X DeSouza (JMIRx Med)
Abstract BackgroundDance has emerged as a complementary treatment that may promote adaptive neural plasticity while improving symptoms of Parkinson disease (PD), such as balance, gait, posture, and walking. Understanding brain changes that arise from participation in dance interventions is important as these neural plastic changes play an important role in protecting and healing the brain. Although dance has been shown to improve PD motor and nonmotor symptoms, the neural mechanisms underlying these changes, specifically depression and mood, remain elusive. Further, many side effects of PD drug treatments can be exacerbated or even induced by dopaminergic drugs, particularly depression and anxiety, making these nonmotor symptoms more noticeable throughout the progression of the disease. ObjectiveIn this study, we focused on the impact of dance interventions on PD nonmotor symptoms by conducting an 8-month observational study, tracking the relationship between depression scores and functional neuroimaging measures for people with PD. MethodsA total of 34 dancers—23 (68%) people with PD and 11 (32%) healthy controls—completed the Geriatric Depression Scale (GDS) before and after attending weekly community-based dance classes, referred to as Dance for PD ResultsDepression scores on the GDS decreased in each preintervention to postintervention comparison (all PPPP ConclusionsThis study contributes to an improved understanding of the neural mechanisms that are involved in depression, as well as the beneficial contribution that longitudinal dance interventions have in reducing nonmotor symptoms associated with PD, particularly in depression symptoms.